Penerapan Sanksi Adat Kajongkokang pada Pengendalian Internal Kredit Macet di Lembaga Perkreditan Desa Adat Sekumpul - Candrasari, Kadek Ladyna; Adiputra, I Made Pradana (Universitas Pendidikan Ganesha, 2021)
This study aims to determine: (1) internal control of credit applied to LPD Desa Adat, (2) the background of the application of customary sanctions Sekumpul kajongkokang as an internal control of bad credit in LPD Desa Adat, (3) application of customary sanctions Sekumpul kajongkokang as internal control bad credit on LPD Desa Adat, (4) implications of the application of customary sanctions kajongkokang Sekumpul as an internal control of bad credit on LPD Desa Adat. This research was conducted using qualitative methods, the data used in this study are primary data and secondary data. The results of this study stated that (1) internal control on LPD Desa Adat applies customary sanctions Sekumpul kajongkokang and related to the internal control component, (2) the background of the application of customary sanctions kajongkokang based on the joint decision of manners village on the imposed awig-awig village to bind and remind the public of its obligations, (3) The application of customary sanctions kajongkokang suspension in the form of customary ceremonial services for krama who have bad credit, (4) the implications arising from the application of customary sanctions kajongkokang that the emergence of shame the emergence of fear, can bind and provide deterrent affect customers, as well as the sanctions, are effective in reducing bad credit in LPD Desa Adat Sekumpul.